PENERAPAN QUICK ON THE DRAW DALAM PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X MIA 3 SMAN 10 PEKANBARU - Fitria Mardika Fitria Mardika; Armis '; Zuhri ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The research is classroom action research that aims to improve mathematics achievement by applying Quick On The Draw in cooperative learning. The subject of this research is student of class X MIA SMAN 10 Pekanbaru in the first semester academic years 2014/2015, there are 40 students in the class, consist of 15 boys and 25 girls. This research is exercised in two cycles, and at the end of every cycle carried out mathematics achievement test. Data collecting through observation for the observation of learning activity of teacher and student and also observation of student attitude, portfolio for the assessment of skill and mathematics achievement test for the assessment of knowledge of student. Base on the result of analysis, the amount of student that reaching KKM at attitude interest improves from 74.36 % at first cycle and become 100 % at second cycle. The amount of student that reaching KKM at knowledge interest improves from early score with percentages 48.71%, at first mathematics achievement test with percentages 56.41% and at second mathematics achievement test with percentages 82.05%. The amount of student that reaching KKM at skill interest improves from 92.3 % at first cycle become 100 % at second cycle. The result of research conclude that applying Quick On The Draw in cooperative learning can improves mathematics achievement of X MIA 3 SMAN 10 Pekanbaru in the first semester academic years 2014/2015 Keywords: Mathematics Achievement, Quick On Tthe Draw, Cooperative Learning, Class Action Research